Correction to: Correlation between functional ability, toe flexor strength, and plantar pressure of hallux valgus in young female adults: a cross-sectional study - Mieko Yokozuka; Kanako Okazaki; Yuko Sakamoto; Koko Takahashi (Journal of Foot and Ankle Research, 2020)
An amendment to this paper has been published and can be accessed via the original article.